Spiritual and Moral Implications of Baptism According to Mark the Hermit - Kamczyk, Wojciech (Collectanea Theologica, 2021)
By taking up the problem of baptism in his writings, Mark the Hermit responds to the tendencies of the Messalians, who denied the value of baptism. Pointing to the consequences of the sacrament, he emphasizes its effectiveness in terms of being rescued from the corollaries of Adam’s sin, restoring freedom and the ability to fulfill the commandments. He emphasizes the priority and efficacy of grace given in a secret manner at the time of baptism. He reminds, however, that baptism does not deprive man of free will, but it can support it in fulfilling the law of God. He also emphasizes the mysterious indwelling of the entire Holy Trinity in the heart of the baptized and its activity. For Mark the Hermit baptism itself also involves “being placed in the paradise of the Church,” which he understands as the ability to perform acts of love towards one’s brothers.